2014
DOI: 10.5120/16685-6801
|View full text |Cite
|
Sign up to set email alerts
|

Study of Data Mining Algorithms for Prediction and Diagnosis of Diabetes Mellitus

Abstract: Diabetes mellitus or simply diabetes is a disease caused due to the increase level of blood glucose. Various available traditional methods for diagnosing diabetes are based on physical and chemical tests. These methods can have errors due to different uncertainties. A number of Data mining algorithms were designed to overcome these uncertainties. Among these algorithms, amalgam KNN and ANFIS provides higher classification accuracy than the existing approaches. The main data mining algorithms discussed in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…In [2], different methods are compared for diabetes detection. Data mining techniques are explored in [8,9] for detection of diabetes. A clinical system is proposed and implemented in [3] for diagnosis of diabetes.…”
Section: Related Workmentioning
confidence: 99%
“…In [2], different methods are compared for diabetes detection. Data mining techniques are explored in [8,9] for detection of diabetes. A clinical system is proposed and implemented in [3] for diagnosis of diabetes.…”
Section: Related Workmentioning
confidence: 99%
“…It was also claimed that HMC and double crossover genetic process based methods were shown better performance to compare other scales. Vijayan et al showed that K-Nearest Neighbor (KNN), K-means, amalgam KNN and ANFIS were used to predict and diagnosis DM [13]. For maximizing expectation in a successive iteration cycle, they used EM algorithm for sampling diabetes data.…”
Section: Related Workmentioning
confidence: 99%
“…Applications using data mining techniques are widely designed, such as the specific disease predicting system for hospital database. Karabatak designed an expert system based for detection of the breast cancer based on association rules and neural network, the system was applied to the Wisconsin breast cancer database [7]. Vijayanv V analyzed and compared some novel data mining algorithms for prediction and diagnose of diabetes mellitus, such as, EM, KNN, K-means, ANFIS and so on, and experimented on Pima Indian Diabetic Set from University of California, Irvine (UCI) Repository of Machine Learning databases [8].…”
Section: Introductionmentioning
confidence: 99%